PENGARUH PROGRAM PEMBERDAYAAN PENDERITA KUSTA BERBASIS SUPPORT GROUP DENGAN PENDAMPINGAN KELUARGA TERHADAP PENINGKATAN KEMAMPUAN PERAWATAN MANDIRI - Henni Kusuma; Susana Widyaningsih; Yuni Dwi Hastuti; Chandra Bagus Ropyanto; Untung Sujianto (LPPM STIKES KENDAL, 2019)
Morbus Hansen (Leprae) is communicable disease which caused by Mycobacterium Leprae. This disease disrupt peripheral nerves, skin, and other body tissues. Blora Regency, Central Java, has the largest of proportion of people with leprosy level 2 disabilities and new cases has increased from year to year. Several findings show that people with leprosy are still not able to perform self-care properly at home so that they experience advanced disabilities that reduce their quality of life. One effort to reduce solve this problem is a patient-family empowerment program in self-care training based on support groups. The purpose of this study is to analyze effect of empowerment among leprae’s patients in Subdistrict Kunduran, District Blora based on support group with family on increasing selfcare competencies. Method of this study is quasy experiment without control group with purposive sampling. Total samples in this study is 8 respondents. This research use leprae’s patients quetionary that has been used by other researcher before. The result show that any significant differences of selfcare competencies between before and after leprae’s patients empowerment program in self-care training use wilcoxon test. Average of pretest score is 55,67 (8-76) and average of posttest is 83,67 (64-100) with p=0,004. Based on this result, so it’s mean that empowerment program in self-care training among leprae’s patients with family based on support group effectively increase selfcare competencies in their home. This therapy can be an innovation on nursing intervention for leprae’s patients.